Gray Matter and Sexes: A Gray Area Scientifically - Angier, Natalie; Chang, Kenneth (The New York Times, 2005)
Harvard Univ president Lawrence H Summers' suggestion that women's lagging progress in science and mathematics might reflect innate differences between sexes inflames debate that has simmered for decades; researchers who have explored subject of sex differences from every conceivable angle and organ say there are host of discrepancies between men and women–in their average scores on tests of quantitative skills, in their attitudes toward math and science, in architecture of their brains, in way they metabolize medications, including those that affect brain; but researchers warn that mere finding of difference in form does not mean difference in function or output inevitably follow; to further complicate portrait of cerebral diversity, new brain imaging studies suggest that men and women with equal IQ scores use different proportions of their gray and white matter when solving problems like those on intelligence tests; photo; graphs (M)